2007
DOI: 10.1159/000098067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cystographic Findings of Intrinsic Sphincteric Deficiency with Urethral Hypermobility Causing Urinary Incontinence

Abstract: Objectives: To evaluate the usefulness of standing and lateral cystograms for differentiation of intrinsic sphincter deficiency (ISD) from urethral hypermobility (UH) causing stress urinary incontinence (SUI). Materials and Methods: 67 female patients with urinary incontinence undergoing measurement of the Valsalva leak point pressure (VLPP) were included. 14 patients with VLPP <60 cm H2O were operated for ISD causing SUI while 53 patients with VLPP >100 cm H2O were operated for UH causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The maximum urethral closure pressure (MUCP) and the Valsalva leak point pressure (VLPP) were used separately and in combination as parameters to study urethral integrity and as outcome predictors in patients who underwent mid-urethral sling operations for SUI [4,5] . At a 3-month follow-up, Miller et al [6] found that TOT was nearly 6 times more likely to fail than TVT when subjects had a preoperative MUCP at or below 42 cm H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum urethral closure pressure (MUCP) and the Valsalva leak point pressure (VLPP) were used separately and in combination as parameters to study urethral integrity and as outcome predictors in patients who underwent mid-urethral sling operations for SUI [4,5] . At a 3-month follow-up, Miller et al [6] found that TOT was nearly 6 times more likely to fail than TVT when subjects had a preoperative MUCP at or below 42 cm H 2 O.…”
Section: Introductionmentioning
confidence: 99%